Long‐term follow‐up of the randomized trial of mesorectal excision with or without lateral lymph node dissection in rectal cancer (JCOG0212). Issue 5 (12th March 2020) - Tsukamoto, S.; Fujita, S.; Ota, M.; Mizusawa, J.; Shida, D.; Kanemitsu, Y.; Ito, M.; Shiomi, A.; Komori, K.; Ohue, M.; Akazai, Y.; Shiozawa, M.; et al.
Abstract : Background: Japan Clinical Oncology Group (JCOG) 0212 (ClinicalTrials.gov NCT00190541) was a non‐inferiority phase III trial of patients with clinical stage II–III rectal cancer without lateral pelvic lymph node enlargement. The trial compared mesorectal excision (ME) with ME and lateral lymph node dissection (LLND), with a primary endpoint of recurrence‐free survival (RFS). The planned primary analysis at 5 years failed to confirm the non‐inferiority of ME alone compared with ME and LLND. The present study aimed to compare ME alone and ME with LLND using long‐term follow‐up data from JCOG0212. Methods: Patients with clinical stage II–III rectal cancer below the peritoneal reflection and no lateral pelvic lymph node enlargement were included in this study. After surgeons confirmed R0 resection by ME, patients were randomized to receive ME alone or ME with LLND. The primary endpoint was RFS. Results: A total of 701 patients from 33 institutions were assigned to ME with LLND (351) or ME alone (350) between June 2003 and August 2010. The 7‐year RFS rate was 71.1 per cent for ME with LLND and 70·7 per cent for ME alone (hazard ratio (HR) 1·09, 95 per cent c.i. 0·84 to 1·42; non‐inferiority P  = 0·064). Subgroup analysis showed improved RFS among patients with clinical stage III disease who underwent ME with LLND compared with ME alone (HR 1·49, 1·02 to 2·17). Conclusion: Long‐term follow‐up data did not support the non‐inferiority of ME alone compared with ME and LLND. ME with LLND is recommended for patients with clinical stage III disease, whereas LLND could be omitted in those with clinical stage II tumours. Abstract : Long‐term follow‐up data did not support the non‐inferiority of mesorectal excision (ME) alone compared with ME and lateral lymph node dissection (LLND). ME with LLND is recommended for clinical stage III disease, whereas LLND could be omitted for patients with clinical stage II tumours. Selective lateral lymph node dissection supported Abstract : Antecedentes: El JCOG0212 (ClinicalTrials.gov : NCT00190541) fue un ensayo fase III de no inferioridad en pacientes con cáncer de recto en estadio clínico II/III sin ganglios linfáticos aumentados de tamaño en la pared pélvica lateral. El ensayo comparó la escisión del mesorrecto ( mesorectal excision, ME) con la ME con disección de los ganglios linfáticos laterales ( lateral lymph node dissection, LLND), siendo el criterio de valoración principal la supervivencia libre de recidiva ( recurrence free survival, RFS). El análisis primario planificado a los 5 años de seguimiento no pudo confirmar la no inferioridad de la ME frente a la ME con LLND. Este estudio tuvo como objetivo comparar la ME como procedimiento único y la ME con LLND utilizando datos de seguimiento a largo plazo del ensayo JCOG0212. Métodos: En este estudio se incluyeron pacientes con cáncer de recto en estadio clínico II/III por debajo de la reflexión peritoneal sin ganglios linfáticos aumentados de tamaño en la pared pélvica lateral. Después de que los cirujanos confirmaran la resección R0 mediante la ME, los pacientes fueron asignados al azar al brazo de ME sola o al brazo de ME con LLND. El criterio de valoración principal fue la supervivencia libre de recidiva (RFS). Resultados: Un total de 701 pacientes de 33 instituciones fueron asignados al azar para ser tratados mediante una ME con LLND ( n = 351) o EM sola ( n = 350) entre junio de 2003 y agosto de 2010. Las tasas de RFS a 7 años fueron del 71, 1% para ME con LLND y 70, 7 % para ME sola (cociente de riesgos instantáneos, hazard ratio, HR: 1, 09 (i.c. del 95% 0, 84‐1, 42), no inferioridad P = 0, 064)). El análisis de subgrupos mostró una mejor RFS entre los pacientes en estadio clínico III que se sometieron a ME con LLND en comparación con ME sola (HR: 1, 49 (i.c. del 95%: 1, 02‐2, 17)). Conclusión: Los datos de seguimiento a largo plazo no justificaron la no inferioridad de la ME en comparación con la ME con LLND. Se recomienda la ME con LLND para pacientes en estadio clínico III, mientras que LLND podría omitirse para pacientes en estadio clínico II.